2004
DOI: 10.2202/1542-0485.1062
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Food Standards as Trade Barriers: Harmonization, Compromise, and Sub-Global Agreements

Abstract: GMOs have brought new concerns into an already challenged world trading system. This paper considers the jointly enodogenous formation of GMO-related standards and sub-global trading agreements. Standards are understood as tolerance levels for GMOs. Sub-global trading agreements may be either formal agreements between countries sanctioned by the WTO, or they may be implicit agreements, e.g. a developing country accepting the U.S. standards.We develop a theoretical model of standard formation and agreement form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Some authors explained GMO standards formation mainly as a function of trade interests. For example, Tothova and Oehmke (2004) developed a Krugmanstyle trade model (Krugman, 1979) that showed that countries select standards taking into account enforcement costs, loss of productivity and loss of trade. Particularly relevant in our context is the two-country partial-equilibrium model developed by technology adoption.…”
Section: Determinants Of Gmo Standards: Theoretical Considerationsmentioning
confidence: 99%
“…Some authors explained GMO standards formation mainly as a function of trade interests. For example, Tothova and Oehmke (2004) developed a Krugmanstyle trade model (Krugman, 1979) that showed that countries select standards taking into account enforcement costs, loss of productivity and loss of trade. Particularly relevant in our context is the two-country partial-equilibrium model developed by technology adoption.…”
Section: Determinants Of Gmo Standards: Theoretical Considerationsmentioning
confidence: 99%
“…Particularly relevant for our analysis are the studies of Cadot et al (2001), Parcell and Kalaitzandonakes (2004), Disdier and Fontagné (2010), Tothova and Oehmke (2004), Veyssiere (2007), and Gruère et al (2009a). 3 Cadot et al (2001) find that the 'regulatory protectionism' aspect of the EU GMO regulation has no repercussions on US export of corn seeds, but has a negative effect on other forms of corn.…”
Section: Introductionmentioning
confidence: 99%
“…They show that the EU moratorium, as well as other European GMO standards, has negative trade effects on the exporting countries. Tothova and Oehmke (2004) develop a Krugman-style trade model to study the endogenous choice of different countries in setting GMO standards, showing the formation of 'clubs' of countries that share similar GMO regulations. These 'clubs' act as sub-global preferential trading agreements.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have pointed out that the stringency of the GMO regulations of big agri-food importers, like the European Union (EU) and Japan, in contraposition with the 'soft' regulations of GMO producers, like the US and Argentina, could represent a serious problem for the developing country' strategy concerning GMO production and regulations (see, e.g., Tothova and Oehmke, 2004;Anderson and Jackson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3 Within this literature, particularly relevant for our analysis are studies by Cadot et al (2001), Parcell and Kalaitzandonakes (2004), Disdier and Fontagné (2008), Tothova and Oehmke (2004), Veyssiere (2007),…”
Section: Introductionmentioning
confidence: 99%